Nipah Resistant Starch (Nypa fruticans), Modulasi Mikroflora Normal Pencernaan dan Pengendalian Diabetes - Vanya Aulia; Pellya Pachira; Monika Olvi; Cico Jhon Karunia Simamora (BIOEDUSCIENCE, 2021)
Background: Gut microbiota in diabetics, the number is in an unstable condition, and sufferers tend to need foods low in calories not to raise blood sugar levels drastically. Nipah grown in coastal areas has a fairly high starch content, potentially as a source of resistant starch that a beneficial colon microbiota can ferment. The purpose of writing this review is to expand knowledge and provide information to the wider community regarding the potential of Nipah, which can be used as a source of new resistant starch that can be used in diabetes and modulation of normal microflora of the body. Method: This review writing procedure is done by searching various literature electronically, namely accessing International and National article searches and books through databases such as Google Scholar, ScienceDirect, and others. The collected data is then processed using Mendeley and then synthetic with narrative methods to conclude (interpretation). Results: Results in the writing of this review, namely obtained Nipah fruit flour with a high enough starch content, which is 35.66%, which has the potential as a source of resistant starch. Conclusion: The writing of this review is that the high content of Nipah starch can be developed into a cheap, resistant starch innovation specifically for people with diabetes.